The Effect of Using Padlet on Student's Writing Skills at Grade VII: Gender Based Differences - Chandra Yane Arlinta; Caroline Victorine Katemba (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
The integration of digital media in writing instruction has become an effective approach to improving students’ learning outcomes. This study employed a quantitative approach using a pre-test and post-test design to analyze the effectiveness of Padlet as a learning medium in teaching writing to seventh-grade students at SMPN 1 Parongpong. The participants consisted of 30 students, including 15 male and 15 female students, and data were collected through writing tests administered before and after the implementation of Padlet. The normality test was conducted using the Shapiro–Wilk test, and the results indicated that all data were normally distributed, with significance values greater than 0.05, namely male pre-test (p = 0.146), male post-test (p = 0.496), female pre-test (p = 0.467), and female post-test (p = 0.085). The findings revealed a significant improvement in students’ writing skills after the use of Padlet, with female students demonstrating a stronger improvement compared to male students, confirming that Padlet is an effective learning medium for enhancing writing skills among seventh-grade students.